Efficacy and safety of pharmacotherapy for recurrent high-grade glioma: a systematic review and network meta-analysis - Xu, Yanan; Guan, Haijing; Yu, Kefu; Ji, Nan; Zhao, Zhigang (Frontiers in Pharmacology, 2023)
Objective: To compare the efficacy and safety of treatments for patients with recurrent high-grade gliomas. Methods: Electronic databases including Pubmed, Embase, Cochrane Library and ClinicalTrials.gov were searched for randomized controlled trials (RCT) related to high-grade gliomas. The inclusion of qualified literature and extraction of data were conducted by two independent reviewers. The primary clinical outcome measures of network meta-analysis were overall survival (OS) while progression-free survival (PFS), objective response rate (ORR) and adverse event of grade 3 or higher were secondary measures. Results: 22 eligible trials were included in the systematic review, involving 3423 patients and 30 treatment regimens. Network meta-analysis included 11 treatments of 10 trials for OS and PFS, 10 treatments of 8 trials for ORR, and 8 treatments of 7 trials for adverse event grade 3 or higher. Regorafenib showed significant benefits in terms of OS in paired comparison with several treatments such as bevacizumab (hazard ratio (HR), 0.39; 95% confidence interval (CI), 0.21-0.73), bevacizumab plus carboplatin (HR, 0.33; 95%CI, 0.16-0.68), bevacizumab plus dasatinib (HR, 0.44; 95%CI, 0.21-0.93), bevacizumab plus irinotecan (HR, 0.4; 95%CI, 0.21-0.74), bevacizumab plus lomustine (90mg/m2) (HR, 0.53; 95%CI, 0.33-0.84), bevacizumab plus lomustine (110 mg/m2) (HR, 0.21; 95%CI, 0.06-0.7), bevacizumab plus vorinostat (HR, 0.42; 95%CI, 0.18-0.99), lomustine (HR, 0.5; 95%CI, 0.33-0.76), and nivolumab (HR, 0.38; 95%CI, 0.19-0.73). For PFS, only the hazard ratio between bevacizumab plus vorinostat and bevacizumab plus lomustine (90mg/m2) was significant (HR,0.51; 95%CI, 0.27-0.95). Lomustine and nivolumab conferred worse ORR. Safety analysis showed fotemustine as the best and bevacizumab plus temozolomide as the worst. Conclusion: The results suggested that regorafenib and bevacizumab plus lomustine (90mg/m2) provide improvements in terms of survival but may have poor ORR in patients with recurrent high-grade glioma.